Application of the Queuing System at the Renon Gacoan Noodle Restaurant (International Journal of Education and Literature, 2024)
Renon Gacoan Noodle Restaurant is a fast food spicy noodle restaurant in Bali. This restaurant, which carries a modern restaurant concept at affordable prices, has made Mie Gacoan Renon popular among various groups. Its strategic location in the city center makes this restaurant busy with visitors, which causes quite dense queues at certain hours. Mie Gacoan Renon uses a Single Channel-Single Phase queuing system to serve visitors. The service also uses a First In First Out (FIFO) model where visitors who arrive first will be served first. The average visitor arrival is 1 person/minute and the average service is 1.6 minutes. With the help of SPSS software In processing the data, it was found that the number of customer arrivals and Mie Gacoan Renon restaurants had a Poisson distribution and the distribution of service times was a Loglogistic distribution.